Pengaruh Kualitas Pelayanan Ditinjau Dari Dimensi Servqual Terhadap Loyalitas Tamu Hotel Sarasvati - Apsari, Farah Afra; Novitaningtyas, Ivo (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Guest loyalty is an important aspect that determines the sustainability of the hospitality business. The purpose of this study was to examine the effect of service quality based on the servqual dimension on guest loyalty at the Sarasvati Hotel, Magelang. This study uses a quantitative approach. The data used are primary data. Primary data was obtained by distributing questionnaires to 50 hotel guests as respondents. The data that has been collected is then analyzed based on multiple linear regression using SPSS. The results of the study indicate that service quality has a simultaneous effect on guest loyalty. Furthermore, among the 5 servqual dimensions, only the tangible dimension has a significant effect on guest loyalty, while the other dimensions, such as responsiveness, empathy, reliability, and assurance, have no effect. The results provide managerial implications for Hotel Sarasvati to improve service quality in the form of tangible aspects such as buildings, facilities, and the appearance of human resources in order to increase guest loyalty